Flow cytometric assessment of the signaling status of human B lymphocytes from normal and autoimmune individuals - Grammer, Amrie C (BioMed Central, 2004)
Abnormalities in lymphocyte signaling cascades are thought to play an important role in the development of autoimmune disease. However, the large amount of cellular material needed for standard biochemical assessment of signaling status has made it difficult to evaluate putative abnormalities completely using primary lymphocytes. The development of technology to employ intracellular staining and flow cytometry to assess the signaling status of individual cells has now made it possible to delineate the perturbations that are present in lymphocytes from patients with autoimmune disease. As an example, human B cells from the Ramos B cell line and the periphery of systemic lupus erythematosus (SLE) patients or normal nonautoimmune controls were assessed for activation of the NF-κB and mitogen activated protein kinase (MAPK) signaling cascades by intracellular multiparameter flow cytometric analysis and biochemical Western blotting. In combination with fluorochrome conjugated antibodies specific for surface proteins that define B cell subsets, antibodies that recognize activated, or phosphorylated inhibitors of κB (IκB) as well as the extracellular regulated kinase (ERK), jun N-terminal kinase (JNK) or p38 MAPKs were used to stain fixed and permeabilized human B cells and analyze them flow cytometrically. Examination of the known signaling pathways following engagement of CD40 on human B cells confirmed that intracellular flow cytometry and Western blotting equivalently assay CD154-induced phosphorylation and degradation of IκB proteins as well as phosphorylation of the MAPKs ERK, JNK and p38. In addition, B cells from the periphery of SLE patients had a more activated status immediately ex vivo as assessed by intracellular flow cytometric analysis of phosphorylated ERK, JNK and p38 when compared with B cells from the periphery of normal, nonautoimmune individuals. Together, these results indicate that multiparameter intracellular flow cytometric analysis of signaling pathways, such as the NF-κB and MAPK cascades, can be used routinely to assess the activation status of a small number of cells and thus delineate abnormalities in signaling molecules expressed in primary lymphocytes from patients with autoimmune disease.